Resistance of tropical black beans to terminal drought. - Frahm, Mark (2003)
A pioneer collaboration between the breedingprograms in Honduras, Mexico and Michigan StateUniversity (MSU) was designed to identify commercial blackbean cultivars exhibiting drought resistance adapted forCentral America and regions in Mexico. Two recombinantinbred line (RIL) populations were developed from crossesbetween a drought resistant line, B98311 from MSU, withTLP 19 and VAX 5, two lines from CIAT with improveddisease resistance and adapted to the growing conditions inLatin America. Both populations were tested (in Zamorano,Honduras and Veracruz, Mexico) under drought stress andnon-stress conditions. Yields were reduced by drought stressand Macrophomina phaseolina, the causal fungal pathogen ofcharcoal rot. Drought stress, disease pressure and low yieldscontributed to the high variation coefficients (VC), whichhindered the identification and selection for superior lines.Selection was based on rank of the geometric mean (GM)yield, calculated from the yield of each line in the stress andnon-stress treatments. The RIL, L88-63 ranked first in GMyield at both locations. Subsequent testing in Honduras andMichigan supported the high yield potential and broadadaptation of L88-63. Breeding for drought resistance inlowland tropical environments will require that additionalresistance to M. phaseolina be incorporated into potentialnew bean lines being considered for release in this region.